Red book : 2003 report of the Committee on Infectious Diseases - 4 0 16; Pickering, Larry K.; 5 Committee on Infectious Diseases (Elk Grove Village, IL : American Academy of Pediatrics, 2003)
Presents a summary of the American Academy of Pediatrics' recommendations concerning infectious diseases in infants, children, and adolescents, including guidelines for immunizations, based on information available as of January 2003.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Infection.;Communicable diseases; 20; 2